ANALYSIS OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES AND ZAKAT COLLECTION UNITS - Riswandi Riswandi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research is a causal quantitative research. The subjects of the study were employees and zakat collection units (UPZ) of Baznas Padang Pariaman Regency and the objects were transformational leadership, work motivation and performance. The population in this study is 75 employees and zakat collection units (UPZ) of Baznas Padang Pariaman Regency. Data was collected using questionnaires and analyzed by path analysis. The results showed that: First, transformational leadership and work motivation have a positive effect on employee performance with an influence of 72.8% Second transformational leadership has a positive effect on work motivation, contribution of influence by 70.0%, third transformational leadership has a positive effect on employee performance with an influence relationship of 61.7%, fourth Work motivation has a positive effect on employee performance with an influence relationship by 34.2%.